Importance of isolated minor findings on fetal ultrasound examinations in the diagnosis of Down syndrome - Gizem Elif Dizdaroğulları; Oya Demirci; Münip Akalın; Özge Kahramanoğlu; Aydın Öcal; Ali Karaman (Perinatal Journal, 2022)
Objective: To investigate the importance of prenatal ultrasound in the detection of Down syndrome by evaluating ultrasonographic and minor ultrasonographic findings in fetuses with this aneuploidy. Methods: Patients who were reported to have trisomy 21 as a result of karyotype analysis performed by cordocentesis, amniocentesis, or chorionic villus biopsy materials and who underwent ultrasound scan before diagnosis between 18 and 26 weeks of gestation by the Maternal Fetal Medicine Department between 2013 and 2020 were included in the study group. Results: The results of 132 of 4525 (2.9%) invasive procedures were reported to have trisomy 21 and ultrasound scans of each fetus were performed in our department. The mean gestational age at the ultrasound scans was 19.2±3.8 (SD) weeks. At least one major structural anomaly or minor ultrasonographic finding was detected in 99.2% of all fetuses. Major structural anomalies were present in 80 (60.6%) fetuses. In fetuses with major structural anomalies, cardiac defects (53.7%) were the most detected anomalies. No ultrasound findings could be detected in one (0.8%) of the remaining 52 patients, and only isolated minor findings were detected in 51 (38.6%) fetuses. More than half (60.7%) of these fetuses had a single minor finding. The most common isolated single minor finding was nuchal fold thickness in 13 (41.9%) fetuses followed by aberrant right subclavian artery in six (19.3%) fetuses. Conclusion: Down syndrome displays a large variety of different sonographic findings on fetal ultrasound. Although major structural anomalies and multiple minor findings are generally considered more important, the presence of any isolated minor marker may be the only detectable finding of Down syndrome.